G129(P) Developing a model for transition in a secondary care trust. (24th May 2017) - Muir, G; Patel, N; Datt, C
Abstract : The prevalence of Children and Young People (CYP) with complex long term conditions is increasing with a consequent requirement for effective transition to adult services. Poor transition can mean poor compliance with treatment and increased morbidity and mortality. Government directives highlight the importance of planning a seamless transfer to adult services. Aim: To develop a Long Term Conditions transition strategy for a Secondary Care Trust Methods: Visiting other Trusts who are chronologically further advanced in transition planning allowed us to become familiar with processes and pathways to follow in our planning as well develop awareness of potential pitfalls. A review of the available literature on transition planning was undertaken. Both exercises provided ideas for good practice to build into our planning. An exercise to review current transition activity for six specialty conditions and to benchmark against the NICE transition guideline was completed. This was undertaken via a questionnaire where the recipient was asked to self-rate their service against statements drawn from the guideline. Results: We identified 19 aspects within the guideline which we could use for the purpose of benchmarking. Results below show the compliance with these areas We identified gaps in the pre/post audit of the process and the transition paperwork. Transition preparation was often at the stage of transfer of care only. GP's were not involved in the transition planning. All areas had transition leads and had links with adult services and were involving colleagues beyond acute services in transition service delivery. Conclusions: Benchmarking provided a useful understanding of transition activity and helped us identify that a generic transition strategy needs the capacity to be individualised to the different services. We are now developing individual action plans face-toface with the service leads to aid better understanding from both sides. There needs to be some flexibility across the individual services to deliver transition for their bespoke patient groups. Objectives will be agreed as to how to meet all areas of the action plan within 6 months. Our intention is to present our completed action plan at conference.